Upaya Guru Dalam Meningkatkan Kualitas Pembelajaran Melalui Penerapan Teknologi Informasi di MI Miftahul Ulum Bago Pasirian - Warda Maghfiroh (JURNAL PETISI (Pendidikan Teknologi Informasi), 2022)
Efforts to improve the quality of education in Indonesia are carried out in various ways. One of them is by changing conventional education into technology-based education. The strategy in improving the quality of education is done by applying information technology in learning in schools. With this application, it will support the learning process that produces skilled students in anticipating the progress of science and technology. The purpose of this study was to find out how teachers and the application of information technology in improving the quality of learning. The research used is a qualitative approach from the results of observations, interviews and documentation. The subject used in this study is the MI Miftahul Ulum Bago Pasirian institution. Based on research conducted by researchers, the roles played by teachers in learning are: first, encouraging students to interact with learning resources or learning media; second, encouraging students to have discussions with their friends; third, asking questions from the teacher to students or students to their friends; fourth, monitoring students' perceptions and thinking processes; fifth, monitor and observe the learning outcomes; sixth, as a mediator in student discussions; and seventh, evaluating to always improve student learning outcomes. This role is accompanied by implementing information technology systems in learning